Acute care utilization risk among older adults living undiagnosed or unaware of dementia. Issue 2 (13th November 2021) - Amjad, Halima; Samus, Quincy M.; Huang, Jin; Gundavarpu, Sneha; Bynum, Julie P. W.; Wolff, Jennifer L.; Roth, David L.
Abstract: Background: Dementia is associated with increased risk of hospitalization and emergency department (ED) visits. Many persons with dementia are undiagnosed or unaware of their diagnosis, however. Our objective was to determine whether undiagnosed dementia or unawareness affects risk of hospitalization or ED visits. Methods: Retrospective longitudinal cohort study of 3537 community‐living adults age ≥65 enrolled in the 2011–2017 National Health and Aging Trends Study with linked fee‐for‐service Medicare claims. Using self or proxy reported diagnosis, proxy dementia screening questionnaire, cognitive testing, and Medicare claims diagnosis, participants were classified as having (1) no dementia or dementia, for which they were classified as (2) undiagnosed, (3) diagnosed but unaware, or (4) diagnosed and aware. Proportional hazards models evaluated all‐cause and potentially preventable hospitalization and ED visit risk by time‐varying dementia status, adjusting for older adult characteristics. Results: Most participants ( n  = 2879) had no dementia at baseline. Among participants with dementia at baseline ( n  = 658), 187 were undiagnosed, 300 diagnosed but unaware, and 171 diagnosed and aware. In multivariable adjusted proportional hazards models, persons with undiagnosed dementia had lower risk of hospitalization and ED visits compared to persons diagnosed and aware (all‐cause hospitalization aHR 0.59 [0.44, 0.79] and ED visit aHR 0.63 [0.47, 0.85]) and similar risks of these outcomes compared to persons without dementia. Individuals diagnosed but unaware had greater risk compared to those without dementia: aHR 1.37 (1.18, 1.59) for all‐cause hospitalization and 1.48 (1.28, 1.71) for ED visits; they experienced risk comparable to individuals diagnosed and aware. Conclusion: Older adults with undiagnosed dementia are not at increased risk of acute care utilization after accounting for differences in other characteristics. Individuals unaware of diagnosed dementia demonstrate risk similar to individuals aware of the diagnosis. Increasing diagnosis alone may not affect acute care utilization. The role of awareness warrants further investigation.